Assistive technology for students with vision impairments - Wan Mohd Saidin, Wan Zalina; Khalifa, Othman Omran (IIUM Press, 2009)
Over the past decade, there has been an increasing recognition that people with disabilities have the same rights to participate in all aspects of community life including education. Technology plays an important role in the lives of individuals with vision impairments. It must be remembered, though, that assistive technology is not the goal, but only the tool to help students reach a series of lifelong solutions. These tools are part of the overall goal for the individual to increase, maintain, or improve functional capabilities, and provide access to one's environment and the general education curriculum. Teachers in all curiculum areas encounter students with a diversity of different educational needs. Particularly, there is a wide variety of Assistive Technology available for students. This paper discusses the development of applications dedicated to the blind users, with the help of reusable components. Developed software that allows visually impaired people to access computer applications is presented. This program reads the contents of each pages, menu or option selected by a user and associates various keys on the keyboard to access each option. It also offers features that enable a user to customize the program according to his or her special need. The methodology relies on component based development. For this purpose, Microsoft text to speech is adapted, have been studied, specified and implemented.